ARSITEKTUR TRADISIONAL BUGIS MAKASSAR (Survei pada Atap Bangunan Kantor di Kota Makassar) - Rahmansah, Rahmansah; Rauf, Bakhrani (Universitas Negeri Makassar, 2014)
Traditional architecture builds upon rules adopted traditions of local communities. Traditional architecture is also a formation of cultural elements that grow and develop along with the growth of a tribe that serve as an identity of the tribe. Traditional architecture should be preserved in order to maintain their extinction. The purpose of this study was to determine changes in the traditional architecture of Bugis Makassar on the roof of an office building in the city of Makassar. Samples were selected intentionally, namely the office of Governor of South Sulawesi, South Sulawesi Provincial Parliament offices, office Makassar City Council, and the Office of PT. PELNI Branch Makassar. Data obtained through field observations, interviews with planning consultants, building users, and tracking documents. The analysis used is descriptive analysis. The results showed that the traditional architecture of Bugis Makassar amended on the roof of the building, namely: a) The shape of the roof, b) color of the roof, c) arrangement timpalaja / sambulayang, and d) the height / slope of the roof.Keywords: Makassar Bugis traditional architecture, roof, change